Utilization System Big Data -Based Pest Prediction in Plants Horticulture : Study Cases in Tropical Regions - Sri Wahyuni Lubis (Digital Agriculture and Innovation Journal, 2025)
Attack difficult pests​ predicted is challenge main in cultivation plant horticulture in tropical regions . Research This aim For evaluate utilization system prediction pest big data based designed For give warning early and recommendations more control​ accurate . Approach research used​ is qualitative with method studies case to three group farmer horticulture in tropical Indonesia. Data collected through interview in-depth , observation field , and documentation use A predictive digital system that integrates microclimate data , field sensors , and machine learning algorithms . Research results show that use system This lower intensity attack pest by 30–50% and increase efficiency use pesticides . Farmers with greater digital literacy tall show level adoption more systems​ good . Findings This give contribution important for development system agriculture adaptive precision​ to change climate tropical and can push taking decision data- based at the level field .